Bending of light in the framework of R+R-2 gravity - Accioly, A.; Azeredo, A. D.; Neto, ECD; Mukai, H. (Sociedade Brasileira Fisica, 1998)
We present a tree level approach to the issue of the deflection of photons by the gravitational field of the Sun, treated as an external field, on the basis of R + R-2 gravity. We show that the deflection angle of a photon grazing the surface of the Sun is exactly the same as that given by general relativity. An explanation for this strange coincidence is provided.